Learners’ Perceptions Towards the Effectiveness of MOOC in Learning Mandarin: 从学习者视角探视MOOC在汉语学习中的应用效果 - Ling, TING Hie; Jun, Ye (Mandarinable: Journal of Chinese Studies, 2000)
The Massive Online Open Course or MOOC was officially launched in Malaysia in 2012. Universiti Teknologi MARA (UiTM), as one of Malaysia's higher education institutions, also involved actively in the promotion of MOOC. Therefore, MOOC UiTM were officially established in 2019. MOOC on Foundation Mandarin (Level II) or MOOC TMC151 is one of the MOOC courses which could be found on the MOOC UiTM. MOOC TMC151 has become as the primary platform neither for the implementation of Online Distance Learning (ODL), nor blended learning during the pandemic. Hence, it is important to explore the effect of the application of MOOC TMC151 in Mandarin learning. To that reason, this study included 36 students who enrolled "Foundation Mandarin (II)" at Universiti Teknologi MARA as respondents to evaluate the effect of the application of MOOC TMC151 in blended learning based on the "Four-level" evaluation of Kirkpatrick Model. Five points Likert scale was utilized to answer the “Four-level” evaluation of Kirkpatrick Model which included “Reaction”, “Behavior” and “Result” level whereas “Learning” level utilized students’ self-evaluate towards their learning in MOOC TMC151. Findings from this study revealed that:(1) For “Reaction” level, students showed their satisfaction with the MOOC TMC151; (2) For “Learning” level, students are more active, which in turn improves their knowledge of Mandarin; (3) There have also been some changes in student behaviour, students found to be test taking, competitive and communicative after the use of MOOC TMC151; (4) At the “Result” level, it was found that students’ performance in Mandarin learning has improved. As a result, students further expressed their desire of using MOOC TMC151 and recommend MOOC TMC151 to friends.